THE USE OF GENERATIVE LEARNING STRATEGY TO IMPROVE STUDENTS' WRITING SKILL IN DESCRIPTIVE TEXT - Agusmaliani; Paula Rombepajung; Tirza A. Kumayas (Faculty of Language and Arts (Fakultas Bahasa dan Seni) Universitas Negeri Manado, 2021)
The aim of this study is to determine whether or not there is an effect on the use of generative learning strategy to improve students’ writing skill in descriptive texts at grade eight of SMP N 6 Tondano. This study involves 30 students consisting 15 students in experimental group and 15 students in control group. This study uses a quantitative research design which is a quasi-experimental research. Data collecting is done by giving a test to write a descriptive text with pre-test and post-test, by students’ in two groups. The mean score of experimental group is 17.73 and control group was 9.6. The data are analyzed using the t-test formula, the results is 5.055. The degrees of freedom is 28 were competency interval 0.05 (95%) is 2.048 and 0,01 (99%) is 2.763. Based on the result, it can be concluded that students’ skill in writing descriptive texts using generative learning increases, but does not increase significantly because from the post-test results on experimental group there are no students’ who are able to achieve score above the KKM. So, the researchers suggest that generative learning strategy should be replaced with other learning strategy.